Contact‐free physiological monitoring using a markerless optical system. Issue 2 (18th May 2015) - Maclaren, Julian; Aksoy, Murat; Bammer, Roland
<x xml:space="preserve">Abstract</x> Purpose Physiological noise remains a major problem in MRI, particularly at higher imaging resolutions and field strengths. The aim of this work was to investigate the feasibility of using an MR‐compatible in‐bore camera system to perform contactless monitoring of cardiac and respiratory information during MRI of human subjects. Methods An MR‐compatible camera was mounted on an eight‐channel head coil. Video data of the skin was processed offline to derive cardiac and respiratory signals from the pixel signal intensity and from head motion in the patient head–feet direction. These signals were then compared with data acquired simultaneously from the pulse oximeter and the respiratory belt. Results The cardiac signal computed using the average image pixel intensity closely resembled the signal obtained using the pulse oximeter. Trigger intervals obtained from both systems matched to within 50 ms (one standard deviation). The respiratory signal computed from small in‐plane movements closely matched the signal obtained from the respiratory belt. Simultaneous MR imaging did not appear to have an effect on the physiological signals acquired by means of the contact‐free monitoring system. Conclusion Contact‐free monitoring of human subjects to obtain cardiac and respiratory information is feasible using a small camera and light emitting diode mounted on the head coil of an MRI scanner. Magn Reson Med 74:571–577, 2015. © 2015 Wiley Periodicals, Inc.